BATIK CIAMISAN: A SOCIOHISTORICAL STUDY WITH A COGNITIVE ONOMASTIC APPROACH - Herlinawati, Lina; Firdaus, Winci (ppjbsip, 2025)
Abstract: Ciamisan Batik is one of the unique cultural heritage in Sundanese Tatars, especially in the Ciamis Regency area, West Java. This article examines Ciamisan Batik through a contemporary socio-historical approach with an emphasis on historical dynamics, cultural identity, and the challenges of globalization. The study was conducted to explore how batik not only functions as a textile artwork, but also as a symbolic representation of the Ciamis community in responding to the changing times. The analysis was carried out by combining qualitative-ethnographic, multimodal, and cognitive onomastics approaches. This approach allows the decipherment of the meaning of names, motifs, and symbols attached to Ciamisan Batik while placing it in the context of today's Indonesian creative economy and cultural politics. The results of the study show that Ciamisan Batik represents a long historical trace of agrarian, colonial, and modern cultural interactions. At a contemporary level, this batik faces the challenges of commodification, industrialization, and changing global market tastes. However, on the other hand, Ciamisan Batik is also a means of cultural diplomacy, a medium for local economic empowerment, and the strengthening of regional identity in the midst of global homogenization. This research makes a theoretical contribution to the development of batik studies based on socio-historical cultural studies and offers a new analytical model that places batik as a living, dynamic, and open cultural text to reinterpretation.